Drought and climate change incidence on hospot Cedrela forests from the Mata Atlântica biome in southeastern Brazil - Venegas-González, Alejandro (2018)
The Atlantic Forest is a Neotropical biome encompassing mainly Brazil's coastline and parts of Paraguay, Uruguay, and Argentina, but today surviving largely in small degraded patches and protected areas. Being a region under threat of extinction of its biological components, little is known about how climate change could influence the biodiversity, dynamics, and stability of this ecosystem. Here, we analyze the response of tree-growth dynamics to regional climate variability and drought, both in temporal and spatial scale. For this purpose, five Cedrela spp forest sites located in the biogeographic region ‘Serra do Mar’ (AFSM) in southeastern Brazil was considered. This region contains the best-preserved secondary forests of the Atlantic Forest biome, a fact that represents a natural laboratory to ascertain the environmental influence on the tree development through large spatial scales. Correlation and regression analysis were used to explore the relationship between growth and rainfall, air temperature, and a drought index. Results indicate that tree growth performance is highly dependent to the dry season rainfall amounts in the most humid sector of the gradient, while sites settled in areas of lower summer temperatures, rainfall during the warm-rainy season is the main determining factor influencing tree-growth dynamics. This implies that the same environmental factor (rainfall) affect differentially the growth of Cedrela sites depending on the sector in the gradient in which they are. We found that the population located at the highest-altitude site experienced a growth decline in recent decades linked to increases of winter regional warming, being more sensitivity to long periods of drought (6–10 years). In summary, the seasonal response of cambium activity in AFSM trees to rainfall varies across a climatic gradient. These results are crucial to understand how the present and future global change may differentially impact on tree population dynamics of montane Neotropical forests.